Drivers of private equity activity across Europe: An East-West comparison - Evžen Kočenda; Shivendra Rai (Charles University in Prague, Institute of Economic Studies (IES), 2023)
We investigate the key macroeconomic and institutional determinants of fundraising and investment activities and compare them across Europe, covering 13 Central and Eastern European (CEE) and 16 Western European (WE) countries. Five macroeconomic variables and nineteen institutional variables are selected. These variables are studied using panel data analysis with fixed effects and random effects models over an eleven-year observation period (2010-2020). Bayesian Model Averaging (BMA) is applied to select the key variables. Our results suggest that macroeconomic variables have no significant impact on fundraising and investment activity in either region. Investment activity is a significant driver of fundraising across Europe. Similarly, fundraising and divestment activity are significant drivers of investments across Europe. Institutional variables, however, affect fundraising and investment activity differently. While investment freedom has a significant effect on funds raised in the WE and CEE countries, government integrity and trade freedom are both significant determinants of investments in both European regions. In addition, the results demonstrate that, in contrast to the WE region, fundraising in the CEE region is not country specific.
Keywords: C11; C23; C52; E22; G15; G24; G28; O16; 330; Private equity (PE); Fundraising; Investment; Central and Eastern Europe(CEE); Western Europe (WE); Bayesian Model Averaging (BMA)